Good boy - Kennedy, Elle; Bowen, Sarina (Kennedy, Elle. WAGS, 2024)
"Hosting her brother's wedding for an MVP guest list is the challenge of Jess Canning's life. Already the family screw-up, she can't afford to fail at this, too. Especially after the colossal mistake she made with the best man during a weak moment last spring. Nobody--absolutely nobody--can find out about that, and there will not be a repeat. Absolutely not. No matter how devastatingly sexy his smile, he's a giant manchild who's never been serious in his life. And if Jess wants to prove herself to her family, serious is what she has to get. For Blake Riley, this wedding is a gift from fate itself. The girl he has his eye on is the maid of honor, and he's the best man? Let the games begin. So what if Jess is giving him a little--fine, a lot--of resistance? He just needs to convince the stubborn blonde that he's really a good boy with a bad rap. Beneath the flirty jokes and goofy smile, he's got layers--even if Jess doesn't want to see them. Luckily, every professional hockey player knows that you've got to make an effort if you want to score. And Jess is just the girl he wants to win." --